Users' Beliefs Toward Physical Distancing in Facebook Pages of Public Health Authorities During COVID-19 Pandemic in Early 2020. (August 2021) - Tan, Soon Guan; Sesagiri Raamkumar, Aravind; Wee, Hwee Lin
This study aims to describe Facebook users' beliefs toward physical distancing measures implemented during the Coronavirus disease (COVID-19) pandemic using the key constructs of the health belief model. A combination of rule-based filtering and manual classification methods was used to classify user comments on COVID-19 Facebook posts of three public health authorities: Centers for Disease Control and Prevention of the United States, Public Health England, and Ministry of Health, Singapore. A total of 104, 304 comments were analyzed for posts published between 1 January, 2020, and 31 March, 2020, along with COVID-19 cases and deaths count data from the three countries. Findings indicate that the perceived benefits of physical distancing measures ( n = 3, 463; 3.3%) was three times higher than perceived barriers ( n = 1, 062; 1.0%). Perceived susceptibility to COVID-19 ( n = 2, 934; 2.8%) was higher compared with perceived severity ( n = 2, 081; 2.0%). Although susceptibility aspects of physical distancing were discussed more often at the start of the year, mentions on the benefits of intervention emerged stronger toward the end of the analysis period, highlighting the shift in beliefs. The health belief model is useful for understanding Facebook users' beliefs at a basic level, and it provides a scope for further improvement.